Effectiveness of telerehabilitation versus home exercise in knee osteoarthritis: a quasi-experimental study in Indonesia - Grenda Aprilyawan; Inayah Ageng Izza; Lanendo Raufbar Ramdan Suwanda; Made Mahaguna Putra (Intelektual Pustaka Media Utama, 2026)
In Indonesia, osteoarthritis affects about 7.30% of the population, with its occurrence rising markedly as people age. The condition is found in 11.08% of individuals aged 45-54 years and increases to 18.85% among those older than 75 years. A large proportion of individuals with knee osteoarthritis (KOA) lead inactive lifestyles and often lack adequate encouragement to engage in physical activity. Exercise is known to be beneficial, as it helps regulate cytokine activity in synovial fluid while reducing inflammation and oxidative stress. This research aimed to evaluate the comparative effectiveness of telerehabilitation and home-based exercise interventions for individuals with KOA. A quasi-experimental approach with pre- and post-intervention assessments and a control group was applied. The study involved 120 participants diagnosed with osteoarthritis, who were assigned to either an intervention group receiving an 8-week telerehabilitation program or a control group performing standard exercises independently. Outcome measures: 30-CST, pain intensity, physical activity levels assessed using IPAQ, fear of movement measured by the Tampa Kinesiophobia Scale, and FSS. These variables were assessed before and after the intervention. Additionally, adherence to exercise (EARS) and patient satisfaction were recorded. Statistical analysis was conducted using the Mann-Whitney test and the Wilcoxon signed-rank test.